Dispersion measure variations in a sample of 168 pulsars - Petroff, E.; Keith, M.; Johnston, S.; van Straten, W.; Shannon, Ryan (2013)
We analyse dispersion measure (DM) variations in six years of radio observations of more than 160 young pulsars, all gamma-ray candidates for the Fermi gamma-ray telescope mostly located close to the Galactic plane. DMs were fitted across 256 MHz of bandwidth for observations centred at 1.4 GHz and across three frequencies – 0.7, 1.4 and 3.1 GHz – where multifrequency observations were available. Changes in dispersion measure, dDM/dt, were calculated using a weighted linear fit across all epochs of available DMs. DM variations were detected at a 3σ level in 11 pulsars, four of which were above 5σ: PSRs J0835−4510, J0908−4913, J1824−1945 and J1833−0827. We find that after 28 years of gradual decline, the DM of PSR J0835−4510 is now increasing. The magnitude of variations in three of the four (PSRs J0835−4510, J0908−4913 and J1833−0827) are above what models would predict for an interstellar medium (ISM) dominated by Kolmogorov turbulence. We attribute this excess as likely due to the pulsar's local environment – the supernova remnants near PSRs J0835−4510 and J1833−0827 and the pulsar wind nebula around PSR J0908−4913. Upper limits were determined for all pulsars without detectable values of dDM/dt, most limits were found to lie above the levels of variations predicted by ISM theory. We find our results to be consistent with scattering estimates from the NE2001 model along these lines of sight.